Teaching opportunities process study of humanities in the context of general cultural competence High School Students (Pedagogy of Higher and Secondary Education, 2012)
Pavlenko І. Teaching opportunities process study of humanities in the context of general cultural competence High School Students.The main aspects of modern psychological-and-pedagogical clarifying didactic potential possibilities concealed in the process of humanities studying in the context of forming high-school pupils’ universal culture  competence. Culture-and-humanity function is defined as a prime one in the regard of forming universal culture competence.
Keywords: didactic potential possibilities; humanities; forming universal culture competence; high-school pupils’ universal culture competence